Simultaneous Elimination of NO by Selective Catalytic Reduction Reaction and Toluene by Oxidation Reaction Over V2O5 -MoO3 /TiO2 Catalysts - Mongkhonsi, Tharathon; Phansadsadee, Thodsaphon (Journal of Advanced Development in Engineering and Science, 2023)
The present research investigated the possibility of simultaneous elimination of NO and toluene coexisted in an exhaust gas stream over V2O5 -MoO3 /TiO2 catalysts. The elimination of NO used the selective catalytic reduction with NH3 reaction while the elimination of toluene used the catalytic oxidation with O2 reaction. The reactions were carried out in the reaction temperature range 120-450°C. The experimental results showed that V2O5 -MoO3 /TiO2 catalysts designed for the elimination of NO using NH3 could simultaneously oxidised toluene. In addition, it was found that when toluene existed in the exhaust gas, the activity for NO removal of the catalysts was greatly enhanced especially in the high reaction temperature region.